1984
DOI: 10.1115/1.3167633
|View full text |Cite
|
Sign up to set email alerts
|

A Parametric Solution to the Elastic Pole-Vaulting Pole Problem

Abstract: The fiberglass pole used in pole vaulting is approximated by an “elastica” having an applied concentrated force and moment at the upper end. Presented is a parametric solution expressed in terms of the tabulated elliptic integrals. The results suggest an advantageous pole-vaulting technique which is not generally recognized by coaches and athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…(2.4) was first presented in [2] and since then has been solved in exact form only for special cases where the bar buckles under the action of concentrated forces and couples at its free end [1,4,10]. Taking into consideration Eq.…”
Section: Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…(2.4) was first presented in [2] and since then has been solved in exact form only for special cases where the bar buckles under the action of concentrated forces and couples at its free end [1,4,10]. Taking into consideration Eq.…”
Section: Formulationmentioning
confidence: 99%
“…On the other hand, the problem of nonlinear buckling analysis (elastica problem) of a straight bar due to terminal loads was first examined by Euler and Lagrange, and since then by many other researchers [1,2,4,10]. In particular, Griner [1] succeeded in constructing a parametric solution of the elastica problem concerning straight bars subjected to compressive forces and couples, while in [10] exact parametric analytic solutions of the same problem were constructed including effects of the transverse deformation. In [4] the authors presented a closed-form solution of the exact third-order nonlinear differential equation (ODE), concerning the elastica analysis of a cantilever due to its own weight, by approximating the slope θ of the deflected elastica up to O θ 2 ; cot θ ∼ = 1/θ .…”
Section: Introductionmentioning
confidence: 98%
“…Many models were studied in order to investigate the stability of the beam models under variety of load cases. Focusing on the simple beam model, there are a number of research works dealing with the postbuckling of the beams under several load cases such as transverse point load [1], axial point load [2][3][4], follower point load [5], uniform load [6], follower uniform load [7], and concentrated moment [8,9]. Majority of previous studies focuses on the postbuckling behaviors of beams under only two specific load cases: point and uniform loads.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrated moments occurring in previous examples may apply at ends or within the span length of the beam depending on design purpose. Griner [8] and Seide [9] have studied a case of beam with the concentrated moments acting at the end. However as aforementioned, in the case of the concentrated moment acting within the span length of the beam, the research regarding to such problem has never been found.…”
Section: Introductionmentioning
confidence: 99%
“…Large flexural deflections of straight bars (elastica problem) can be solved in terms of elliptic functions and integrals when the loads consist of concentrated end forces and couple [1][2][3]. In Ref.…”
Section: Introductionmentioning
confidence: 99%